Indirect Impacts of COVID-19 on a Tropical Lobster Fishery’s Harvest Strategy and Supply Chain - Plagányi, Éva; Deng, Roy Aijun; Tonks, Mark; Murphy, Nicole; Pascoe, Sean; Edgar, Steven; Salee, Kinam; Hutton, Trevor; Blamey, Laura; Dutra, Leo (Frontiers in Marine Science, 2021)
The Torres Strait tropical rock lobster Panulirus ornatus (TRL) fishery is of immense social, cultural and economic importance to the region’s Indigenous fishers from both Australia and Papua New Guinea (PNG). During 2020, the COVID-19 pandemic indirectly impacted this fishery as well as a number of other fisheries reliant on international export markets. The TRL fishery is managed using an empirical (data-based) Harvest Control Rule (eHCR) to rapidly provide a recommended biological catch (RBC), based on catch, fishery-independent survey indices and catch-per-unit-effort (CPUE). Here, we summarize the impacts of COVID-19 on each of these critical data inputs and discuss whether the eHCR was considered adequately resilient to this unprecedented disruption to the system. Next, we use a quantitative supply chain index to analyze the impact of disruptions to the supply chain, and inform on potential adaptation strategies. The catch and CPUE data were impacted to varying degrees by external constraints influencing fishing effort, but the fishery-independent survey wasn’t affected and hence there remains an unbroken survey time-series for the fishery extending back to 1989. The eHCR was shown to be reasonably robust because it incorporates longer-term trends over a 5-year period, and accords substantially more weighting (80%) to the fishery-independent survey rather than CPUE data which can be affected by trade and other disruptions. Despite the eHCR not having been tested for scenarios such as a global pandemic, this robustness is a positive given the types of disruptions we will likely face in future climate. The weak links identified in the supply chain were the same as those previously highlighted as sensitive to climate change disruptions. Our supply chain analysis quantifies the impact on system resilience of alternative paths connecting producers to consumers and reinforces that supply chains may be particularly vulnerable to external disruptions if they are not sufficiently diverse.